Identification of larvae of two Aphodius Helwig, 1798 (Coleoptera: Scarabaeidae: Aphodiinae) species using morphology and DNA barcode - Frolov, Andrey V.; Vishnevskaya, Maria S.; Akhmetova, Lilia A. (Zootaxa, 2021)
The third instar larvae of Aphodius (Alocoderus) hydrochaeris (Fabricius, 1798) and A. (Bodilus) ictericus (Laicharting, 1781) are described based on scanning electron microscopy and COI sequences. COI barcode sequence for A. (A.) hydrohaeris is provided for the first time. Two haplotypes are discovered in A. (B.) ictericus.